Examining Vocabulary Usage Ratios of CEFR Vocabulary and AWL vocabulary in Comparison to CEFR Proficiency Levels among Pakistani EFL Writers and Offering Instructional Recommendations for Vocabulary Items - Muhammad Taimoor A.A.Gurman, Muhammad Taimoor A.A.Gurman; Azmi Abdul Latiff, Azmi Abdul Latiff; Ishfaque Ahmed Abbasi, Ishfaque Ahmed Abbasi; Zahid Ali Jatoi, Zahid Ali Jatoi; Choudhry Shahid, Choudhry Shahid (2023)
The purpose of this research was to investigate the vocabulary profiles of written English compositions produced by Pakistani EFL students studying at the university level. Eleven students who were enrolled in higher education institutions took part in this research. According to the CEFR, six of the students were at the B2 level, three were at the C2 level, and two were at the C1 level. The primary data for this investigation was taken from students' written works. The texts that were included in this investigation were written under regulated circumstances (with regard to both their subject matter and their overall length) and were categorised according to their CEFR level (B2, C1, and C2). A comparison of vocabulary profiles for textual compositions derived from AWL and EVP wordlists was carried out for the purpose of this research by utilising EVP Text-Inspector (Text inspector). It was discovered that there seemed to be a little change in the percentages of AWL tokens between low and high CEFR levels, but it was discovered that there was no significant difference in the vocabulary that was employed from the CEFR wordlist of EVP